Analysis of direct mechanical into thermal energy conversion using eddy currents - Golovko, V.; Mikhalin, V. (Energy and Automation, 2025)
The article presents the results of an experimental study on the operation of an induction heat energy generator, which implements the conversion of mechanical energy from the rotation of a magnetic disk into thermal energy through eddy currents induced in a conductive metal plate by an alternating magnetic field. The object of the research is the process of direct conversion of mechanical energy into heat. The experimental setup consists of a rotor with permanent magnets arranged in a circular pattern, rotating above a steel plate. As the magnetic field moves relative to the conductor, eddy currents are induced, resulting in heating due to Joule losses. The influence of the structural and magnetic parameters of the setup on the amount of thermal loss power is investigated, particularly the frequency of magnetic field variation, the magnetic flux density, and the distance to the plate. To verify the experimentally obtained values, a theoretical formula for calculating eddy current power loss was used, which accounts for the magnetic induction, frequency of field variation, and the electrical properties of the material. A comparison between theoretical and experimental results showed a discrepancy of less than 10%. The obtained results can be applied in the development of contactless heating systems, energy recovery systems, and power units with direct mechanical-to-thermal energy conversion, especially for wind and hydraulic turbines. Key words: renewable energy sources, wind energy, induction heating, eddy currents, permanent magnets, heat energy generator, contactless heating, direct energy conversion, rotational motion